2000
DOI: 10.1080/02699930050117693
|View full text |Cite
|
Sign up to set email alerts
|

Prospective cognitions in anxiety and depression: Replication and methodological extension

Abstract: The present study presents a replication and methodological extension of MacLeod, Tata, Kentish, and Jacobsen (1997) with a nonclinical sample, using future-directed imagery to assess prospective cognitions. Results showed that only anxiety (but not depression) was related to enhanced imagery for future negative events. Both anxiety and depression showed significant zero-order correlations with reduced imagery for future positive events. However, when the overlap between anxiety and depression was controlled f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

27
126
4
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(158 citation statements)
references
References 10 publications
27
126
4
1
Order By: Relevance
“…Furthermore, there is evidence that people with a long-term tendency towards (trait) anxiety and/or current (state) anxiety (Q4) judge ambiguous stimuli as more likely to be negative, while people in states of sadness or depression (Q3) judge them as less likely to be positive in line with predictions outlined above (e.g. MacLeod et al 1997;Stober 2000;MacLeod & Salaminiou 2001). There is also evidence that people in positive moods show optimistic forms of these so-called 'cognitive biases' (e.g.…”
Section: Integrating Discrete and Dimensional Approachessupporting
confidence: 61%
“…Furthermore, there is evidence that people with a long-term tendency towards (trait) anxiety and/or current (state) anxiety (Q4) judge ambiguous stimuli as more likely to be negative, while people in states of sadness or depression (Q3) judge them as less likely to be positive in line with predictions outlined above (e.g. MacLeod et al 1997;Stober 2000;MacLeod & Salaminiou 2001). There is also evidence that people in positive moods show optimistic forms of these so-called 'cognitive biases' (e.g.…”
Section: Integrating Discrete and Dimensional Approachessupporting
confidence: 61%
“…The suppression of visual imagery has been proposed as an important cause of anxiety maintenance (Borkovec, Ray, & Stober, 1998). Stober (2000) asked non-clinical participants to form a visual image of hypothetical negative events and found that ratings of imagery vividness, detail and speed of access were positively correlated with trait anxiety scores on the State-Trait Anxiety Inventory (Spielberger, Gorsuch, Lushene, Vagg, & Jacobs, 1983). A methodological weakness of this interesting study is that there was no check that participants actually formed a visual image.…”
Section: © 2005 John Wiley and Sons Ltdmentioning
confidence: 96%
“…Different variations and adaptations of the SPT have been used in research (e.g. Boselie et al, 2014;Hanssen et al, 2013;Stöber, 2000). The original authors developed a revised version by increasing the number of positive items (from 10 to 14) and reducing the number of negative items (from 20 to 16).…”
Section: Introductionmentioning
confidence: 99%